The Influence of Applying the Baby-Led Weaning (BLW) Method in the Feeding of Complementary Feeding in Infants - Harwin Holilah Desyanti; Fadilatus Siriah (Jurnal Health Sains, 2023)
Baby-Led Weaning is a method to introduce complementary foods to babies aged 6 months or older. Weaning or the introduction of complementary foods of breast milk can be a major role in the future growth and health of the baby. This research design uses the Literature Review method. The articles were obtained from keyword searches in the Google Scholar, Pubmed and Scient Direct databases with publications ranging from 2018-2022 in English. The results of the study which are in accordance with the inclusion state that the Baby-Led Weaning method is very influential in giving MP-ASI from an early age to infants. The results of the analysis of 5 journals found that the use of the baby Led Weaning method affects nutritional intake, oral motor development, and body weight, besides that it affects the duration of feeding and even affects the incidence of choking.